Vaccine solutions to East Coast fever for smallholder farmers in Tanzania - Kiara, Henry K. (International Livestock Research Institute, 2016)
Henry Kiara, a veterinary epidemiologist at ILRI, explains his work and how it is helping smallholder farmers in Tanzania battle East Coast fever.